2006
DOI: 10.1007/s11011-006-9007-4
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype-dependent susceptibility of cholinergic neuroblastoma cells to neurotoxic inputs

Abstract: A preferential loss of brain cholinergic neurons in the course of Alzheimer's disease and other encephalopathies is accompanied by a proportional impairment of acetyl-CoA synthesizing capacity in affected brains. Particular susceptibility of cholinergic neurons to neurodegeneration might results from insufficient supply of acetyl-CoA for energy production and acetylcholine synthesis in these conditions. Exposure of SN56 cholinergic neuroblastoma cells to dibutyryl cAMP and retinoic acid for 3 days caused their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(87 citation statements)
references
References 40 publications
3
82
0
2
Order By: Relevance
“…Subsequently, the replenishment of the cellular ACh reservoir by its synthesis from acetyl-coenzyme A (CoA) and choline takes place. Because acetyl-CoA is not only used for ACh synthesis in these cells but also for energy and membrane phosphatidylserine synthesis (47), any shortage or insufficient supply of acetylCoA will result in either reduced transmitter activity by impaired ACh synthesis or in cellular degradation. Furthermore, cholinergic cells might use the choline bound in the cell membrane to produce ACh in cases of acetyl-CoA deficiency (53).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the replenishment of the cellular ACh reservoir by its synthesis from acetyl-coenzyme A (CoA) and choline takes place. Because acetyl-CoA is not only used for ACh synthesis in these cells but also for energy and membrane phosphatidylserine synthesis (47), any shortage or insufficient supply of acetylCoA will result in either reduced transmitter activity by impaired ACh synthesis or in cellular degradation. Furthermore, cholinergic cells might use the choline bound in the cell membrane to produce ACh in cases of acetyl-CoA deficiency (53).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, high activity of PDHC in neuronal cells would secure generally higher, transmitter type-independent energy demands of these brain cells irrespective of the synthesized transmitter. However, such feature of PDHC expression in neurons would make cholinergic ones more vulnerable than noncholinegric ones to neurodegeneration due to utilization of additional fraction of acetyl-CoA for ACh synthesis (next chapter) [6, 71]. …”
Section: Intercellular Compartmentalization Of Brain Acetyl-coa Metabmentioning
confidence: 99%
“…Cells transfection with additional copy of ChAT cDNA caused several fold elevations of ChAT activity and ACh content and over twofold decrease of whole cell acetyl-CoA. Thus, there is an inverse correlation between expression of cholinergic phenotype and size of acetyl-CoA pool in the cholinergic neurons [71, 75]. Highly cholinergic cells contain of less NAA, due to lower concentration of acetyl-CoA in their mitochondria decreasing velocity of aspartate-N-acetyltransferase reaction (EC 2.3.1.17.)…”
Section: Intercellular Compartmentalization Of Brain Acetyl-coa Metabmentioning
confidence: 99%
“…It has been demonstrated that aluminium interferes with the metabolism of acetyl-CoA, leading to a decrease in mitochondrial acetyl-CoA content [110]. As elevated cholinergic activity stimulates acetyl-CoA synthesis in order to supply it for synthesis of acetylcholine, the deleterious effects of aluminium on this metabolic pathway are more prominent in cholinergic nerve terminals [111][112][113]. The choline used for the synthesis of acetylcholine is either transported from the synaptic cleft (see Section 6) to the presynaptic nerve terminal or is derived from phosphatidylcholine.…”
Section: Neurotransmitter Synthesis and Storagementioning
confidence: 99%